A case study of a rubber and pepper reprocessing factory in East Malaysia - Anonymous, - (1981)
This is a micro-case study of a rubber and pepper reprocessing factory in East Malaysia. The major aspects of the study concern mainly the work environment, the labour force and the relations between the management and the workers. Although the working conditions in factory X are better when compared with the working conditions in many other factories in this region, they are still comparatively low when one measures these working conditions (such as hours of work, bonus, income, etc.) against the workers ' contributions as well as the present inflation rates. Factory X has expanded manifold since its inception more than ten years ago. Yet, the salaries of the "Pioneers" (workers who worked here since factory X was first established) has not increased proportionately. The total production of rubber and pepper has increased tremendously recently as a result of high overseas demand. As a result, a subsidiary branch was established in Singapore to facilitate distribution and export. More than 70% of the work force is made up of the temporary workers with the majority of them being the females. A large portion worker of these female workers are young school-dropouts and many of them are also under aged. The temporary workers are the worst off since they do not enjoy the fringe benefits (such as bonuses, paid sick- leave, maternity paid leave, etc.) which are enjoyed by the permanent workers. As a result of their low salaries, these female workers have to take up part- time jobs to supplement their low incomes. Moreover, they also have to do household chores and attend to the needs of their children. Perhaps, over-work may have serious health implications for fatigue can cause lack of alertness which, in turn, may lead to accidents. The poor working conditions coupled with the low salary have subsequently given rise to discontentment among the workers. With the indifferent attitude of their supervisors to alleviate their problems and the lack of understanding of the management to listen to their appeals for increase in salary, bonus, etc., the gap between the management and workers has widened further. Dissatisfaction among the workers has also led them to adopt “mild” sabotage in the form of wastage of resources and time. Sometimes, violence also erupts between the supervisors and the workers. Consequently, many workers leave their jobs and work anywhere.